Myo-inositol increases respiratory burst, cellular proliferation, and phagocytosis of cultured leukocytes from Nile tilapia - Edgar Junio Damasceno Rodrigues; Pedro Luiz Pucci Figueiredo de Carvalho; Vitor Fernandes Silva; Delbert M. Gatlin, III; Margarida Maria Barros (Comparative Immunology Reports)
Myo-inositol (MI) is a functional nutrient known to positively affect growth and health parameters when supplemented in appropriate concentrations. This bioactive molecule plays an essential role by modulating several signaling pathways including those related to some immunological responses. Therefore, this study aimed to evaluate the effects of MI supplementation on immunological responses of Nile tilapia head-kidney-derived leukocytes. Primary cell cultures of head-kidney leukocytes were used to evaluate respiratory burst, cell proliferation, and phagocytosis. Five concentrations of MI were supplemented to the culture media: 0, 300, 600, 900, and 1200 mg l-1 with 16 replicates per concentration. MI supplementation at 900 mg l-1 increased intracellular anion superoxide production up to 15 %, whilst 1200 mg l-1 boosted extracellular anion superoxide production up to 39 % in comparison with the basal group. The phagocytic capacity of cultured cells supplemented with 1200 mg l-1 MI was improved by 24 % in comparison with the basal group. Proliferative responses also were enhanced by approximately 47 % when cells were supplemented with 900 mg l-1 of MI. Quadratic regression analysis determined 872 mg l-1 to be the optimum supplementation level of MI for leukocyte proliferation. Based on the results of all measured responses, 900 mg l-1 of MI was considered the optimal supplementation level for stimulating immunological functions of cultured Nile tilapia leukocytes. The findings of this study provided evidence of both the positive effects of MI and its role in modulating immunological responses of leukocytes highlighting MI potential as an immunomodulatory aquafeed additive.